Endogenous Cannabinoid Production in the Rat Female Reproductive Tract Is Regulated by Changes in the Hormonal Milieu - Cassandra Allard; Heather B. Bradshaw (MDPI AG, 2011)
The endogenous cannabinoid (eCB) system is emerging as an important component of female reproductive tract physiology. The eCBs anandamide (AEA), 2-arachidonoyl glycerol (2-AG), and N-arachidonoyl glycine (NAGly) were measured in the rat reproductive tract at five time points in the four-day estrous cycle, in acyclic retired breeders (RB), after ovariectomy (OVX), OVX + estrogen (E2), OVX + progesterone (P4), or OVX with E2+P4. eCBs were measured in the uterus, uterine adipose, ovaries, and ovarian adipose using HPLC/MS/MS. Levels of AEA, 2-AG, and NAGly were highest in the estrus phase of the estrous cycle in the uterus, whereas, only NAGly had differences in production in the ovaries across the cycle. All eCBs were lower in RB ovaries; however, the production of eCBs in the uterus of RB and OVX groups was more varied with NAGly showing the lowest levels of production in these groups. Levels of AEA in uterine fat were significantly higher or equivalent to levels in the uterus. However, levels of 2-AG and NAGly were dramatically lower in uterine fat verses the organ. Ovarian fat had significantly lower levels of all three eCBs. These data provide evidence that the hormonal milieu plays a significant and complex role in the production of eCBs in the female rat reproductive tract.